The Shift from Traditional Marketing to Entrepreneurial Marketing Practices: A Literature Review - Abdul Rahim, H.; Ab. Wahab, K.; Saad, Abidah (Redfame Publishing, 2015)
Small and medium enterprise(SME) have always been an interesting subject for research. In comparison to larger business organizations, SMEs faced many challenges including how they manage daily marketing activities and make marketing related decision. This study compiles the related literature review on the issues of traditional marketing and entrepreneurial marketing. Purpose: This study aims to explore the role of marketing practices in small and medium sized enterprises (SMEs) and to evaluate the impact of changes in marketing practices from traditional to entrepreneurial marketing practices will have an impact on the SME performance. Research methodology: A compilation of related literature review on traditional marketing and entrepreneurial marketing was done. An observation on the changes in marketing practices in small and medium enterprises towards a more innovative marketing practice were identified. Findings: Marketing in SMEs is centered on traditional methods such as using print media and hard selling. SME owners should take account of the findings and work towards introducing SME-specific marketing practices in trying to achieve higher sales volume and growth. In the study area which is Klang Valley, Malaysia the shift from traditional marketing to entrepreneurial marketing was observed amongst the SMEs being studied. Research limitations: This study uses a small number of SME companies in one region and therefore the generalizability of the findings may be limited. Further research could extend the number of SME companies and to other regions of Malaysia. Practical Implications: The findings have a bearing on the Malaysian SME performance. This study offers insights into how the marketing practices in Malaysian SMEs needs to be adapted in light of the findings to ensure marketing practices of SMEs are compatible with current digital approaches.